Off-label use of drugs administered by enteral feeding tubes in an Intensive Care Unit in Fortaleza, Brazil - Gabriela A. ABREU (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To analyze the prescription profile of drugs administered through enteral feeding tubes in an adult intensive care unit and gather recommendations for their safe administration. Methods: This is a descriptive and retrospective study conducted with adult critical clinical patients of a university hospital in Fortaleza-Ceará from March to May 2018. We performed analyses of patients’ medical records and prescriptions regarding drugs, pharmaceutical presentations and the possibility of administration through enteral tubes. Results: 489 prescriptions containing 1914 items were evaluated, from which 16.6% (n = 318) through tubes. Medicines for the cardiovascular system (34.6%), nervous system (27.4%) and digestive system and metabolism (15.1%) were the most predominant, with an average of 5.8 (DP: 4.2) different per patient. Regarding the pharmaceutical presentation, oral solids were frequently prescribed via enteral tube (67.9%), especially risperidone (8.8%), carvedilol (8.3%) and amiodarone (7.9%). There were contraindications for administration through tubes in 21.6% of solid oral formulations, while there were alternative standardized pharmaceutical forms in the hospital for 43.1%. In addition, substitution for liquid preparations from the market were possible in 43.1%. Among those to which there were no alternative formulations, drugs targeting the cardiovascular system prevailed (52.2%). A table with guidelines for the proper administration of the prescribed solid medications was elaborated then. Conclusion: Solid oral medications were frequently prescribed through enteral tubes, especially those for the cardiovascular system without alternative formulations, which shows the need for guidelines to promote the safety of this process.